DYNAMICS OF DENSITY INHOMOGENEITIES IN THE MANTLE - Karakin A.V.; Tolkunova T.L. (My University, 1987)
A discussion is presented of the problem of the ascent of a certain volume (body) of light matter in a homogeneous upper mantle. Experimental data indicate that during ascent, the upper boundary should be deformed and change shape. As the body of light matter approaches the upper boundary it should spread, producing a partially melted asthenosphere. Thus our results apply mainly to continental zones of tectonic activation, which are intermediate between orogenic belts and cold ancient crystalline shields. In these regions the lithosphere is fragmented and its lower zone is heated, so that it has a rather low viscosity, of the order of 1022-1023 P, which may prove similar to that of the upper mantle.